2005
DOI: 10.4102/ojvr.v72i3.204
|View full text |Cite
|
Sign up to set email alerts
|

Small mammals as hosts of immature ixodid ticks

Abstract: <span style="font-family: arial,helvetica;">Two hundred and twenty-five small mammals belonging to 16 species were examined for ticks in Free State, Mpumalanga and Limpopo Provinces, South Africa, and 18 ixodid tick species, of which two could only be identified to genus level, were recovered. Scrub hares, <em>Lepus saxatilis</em>, and Cape hares, <em>Lepus capensis</em>, harboured the largest number of tick species. In Free State Province Namaqua rock mice, <em>Aethomys nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 9 publications
2
23
1
3
Order By: Relevance
“…This is in agreement with the findings of previous studies which indicated that eastern rock sengis were hosts for a large variety of parasite species, particularly ticks (Fourie et al 1992(Fourie et al , 1995(Fourie et al , 2005Beaucournu et al 2003;Harrison et al 2011). Species richness was greatest in summer possibly because the rainfall and elevated temperatures favoured a number of the ectoparasite species encountered.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in agreement with the findings of previous studies which indicated that eastern rock sengis were hosts for a large variety of parasite species, particularly ticks (Fourie et al 1992(Fourie et al , 1995(Fourie et al , 2005Beaucournu et al 2003;Harrison et al 2011). Species richness was greatest in summer possibly because the rainfall and elevated temperatures favoured a number of the ectoparasite species encountered.…”
Section: Discussionsupporting
confidence: 92%
“…The 11 tick species recovered in the present study represent the largest number of species recovered from eastern rock sengis at a single locality. Sengis are amongst the preferred hosts of the immature stages of R. arnoldi and R. warburtoni, and virtually the sole hosts for the immature stages of R. nuttalli (Walker et al 2000;Fourie et al 2002Fourie et al , 2005. The prevalence of these ticks in the present study supports this fact.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Various wild and domestic carnivores are the preferred hosts of the adults of H. elliptica, including domestic dogs and cats as well as lions (Panthera leo), leopards (Panthera pardus) and cheetahs (Apanaskevich et al, 2007;Horak et al, 1987;Horak et al, 2000;Horak and Matthee, 2003;Horak et al, 2010). Several murid rodent species are the preferred hosts of its immature stages (Hoogstraal, 1956;Horak et al, 2005;Petney et al, 2004). Although Jacobs et al (2004) demonstrated that this tick can complete more than one life cycle annually under laboratory conditions, they doubted whether this would occur in nature.…”
Section: A Hebraeummentioning
confidence: 99%